Application of Microwave Heating in Biomass Hydrolysis and Pretreatment for Ethanol Production - Hermiati, Euis; Mangunwidjaja, Djumali; Sunarti, Ttiti C; Suparno, Ono; Prasetya, Bambang (ANNALES BOGORIENSES, 2010)
Recently, due to depletion of  fossil derived energy stock in the world, there are growing  interests in utilizing biomass sources of bioethanol. There are basically two types of biomass that are usually used or converted to ethanol, starchy and lignocellulosic biomass. The conversion of starchy and lignocellulosic materials are widely explored,  however,  there  are  still  some  drawbacks,  such  as  high  enzyme  cost  and  intensive  energy  needed. Therefore, lower cost as well as energy and time efficient process technology in biomass conversion to ethanol  is important in enhancing the use of biomass to substitute fossil fuel. Microwave heating offers some advantages to overcome these drawbacks, especially due to its quick heat transfer and its heating selectivity. In conventional heating the  heat  was  transferred  through  conduction  or  convection  process  which  took  longer  time.  Thus,  by using microwave, degradation of starchy and lignocellulosic biomass could be completed in shorter time than by using conventional heating method. The roles of microwave heating in the degradation of biomass, especially starchy and lignocellulosic biomass  and its relation to the hydrolysis and pretreatment of that particular biomass for ethanol production are reviewed and discussed.   Keywords: biomass, pretreatment, ethanol, microwave